Evaluation of resistance of teeth subjected to fracture after endodontic treatment using different root canal sealers: An in vitro study - S S Bhat; S K Hegde; A Rao; A K Shaji Mohammed (Wolters Kluwer Medknow Publications, 2012)
Aims: The aim of this study was to compare the ex-vivo effects of different root canal sealers on the fracture resistance of endodontically treated teeth. Materials and Methods: Seventy-five freshly extracted human mandibular premolars were used for the study. The length was standardized to 14 mm and all the teeth were biomechanically prepared and divided into five different groups based on the type of root canal sealers used. Group I:- Roeko seal + gutta percha, Group II: AH plus ® root canal sealer + gutta percha, Group III: PULPDENT root canal sealer + gutta percha, Group IV: Zinc oxide-eugenol sealer + gutta percha, Group V: Control (unobturated teeth). The teeth were embedded in acrylic resin blocks and compressive strengths were measured using universal testing machine (Instron). Statistical Analysis Used: One-way ANOVA, unpaired t- test Results: Data obtained were statistically evaluated using one-way ANOVA and unpaired t-test. All groups showed a statistically significant result (P < 0.05). Teeth obturated with Group I and Group II showed higher resistance to fracture than teeth obturated with other three Groups. It was seen that the teeth obturated with group III showed a better fracture resistance than Group IV and there was no statistical significance found between Group and Group V. Conclusions: From this study, it has been concluded that both the resin based sealers that were used in this study were equally effective compared to that of the zinc oxide-based sealers and the control group. However, no significant results were obtained when the comparison was made between zinc oxide-eugenol and gutta-percha and the control group.